UNDERSTANDING OUR PAST IN THE SCHOOL EXPERIENCE Afro-Caribbean schools in Costa Rica - Castillo Serrano, Deyanira (Universidad de Costa Rica, 2011)
This article is one of series which main goal is to develop an historical portrayal of schools for Afro-Caribbean people in Costa Rica during the first half of the 1900s. The focus of the articles is based on an oral history investigation that envolves around four key questions: 1) What were the schools of the Afro-Caribbean people in Costa Rica like during the 1934-48? 2) How were they started? 3) What curriculum was taught in those schools? How was it taught ? 4) What happened to those schools over time? The selected site for the study was Limon, Costa Rica. This city has been the place of arrival and dwelling of most of the country’s Afro-Caribbean people since 1872. The qualitative methods used provided evidence to answer the research questions. Among the techniques of data collection were open-ended interviews, recording of the interviews, verbatim transcriptions of those interviews, literature review, and various documents. The interviews followed the guidelines of oral history inquiry (i.e., with consent and agreement forms pre-signed). The data collected revealed that the English Schools(as they were known in Costa Rica) were supported by different church denominations, the railroad company, the United Fruit Company, and the Universal Negro Improvement Association. A description of the general organization and the curriculum and instruction practiced permitted to find similarities between the English Schools and the primary schools designed for the British colonies, particularly Jamaica. This first article of the series talks briefly about the general context of the English Schools and the roll that these entities played supporting the schools.